1979
DOI: 10.1073/pnas.76.9.4375
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and regulation of reductase kinase, a protein kinase that modulates the enzymic activity of 3-hydroxy-3-methylglutaryl-coenzyme A reductase

Abstract: was associated with significant loss of radioactivity and enzymic activity in the protein band ascribed to reductase kinase. These results provide evidence that the activity of reductase kinase, like HMG-CoA reductase, is modulated by a reversible phosphorylation-dephosphorylation reaction sequence. Recently, we (1) demonstrated that the enzymic activity of rat liver microsomal 3-hydroxy-3-methylglutaryl-coenzyme A reductase [HMG-CoA reductase; mevalonate:NADP+ oxidoreductase (CoA-acylating), EC 1.1.1.341 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…could be resolved from AMPK on DEAE-Sepharose (66). Fractions containing AMPK and the putative upstream kinase were also separated by Beg et al (21). These studies indicated that the system was a protein kinase cascade in which an upstream kinase (now termed AMPKK) phosphorylated and activated the downstream kinase (AMPK).…”
Section: Amp-activated Protein Kinase: Studies Of Regulation In Vitromentioning
confidence: 90%
“…could be resolved from AMPK on DEAE-Sepharose (66). Fractions containing AMPK and the putative upstream kinase were also separated by Beg et al (21). These studies indicated that the system was a protein kinase cascade in which an upstream kinase (now termed AMPKK) phosphorylated and activated the downstream kinase (AMPK).…”
Section: Amp-activated Protein Kinase: Studies Of Regulation In Vitromentioning
confidence: 90%
“…The procedure used was essentially the bromodeoxyuridine-visible light method of Kao and Puck (8). CHO-KI cells grown in F12 medium/8% FC were mutagenized by 0.4 ,l ethyl methane sulfonate/ml of medium in 100-mm Lux petri dishes containing 2.5 X 106 cells for 16 hr and then incubated and passed when necessary for a period of [5][6][7] days to permit expression of a mutant phenotype. The cells were pooled, and 25,000 cells were inoculated into each of forty 60-mm petri dishes in F12 medium/8% FC and incubated for 4 hr to permit their attachment.…”
Section: Methodsmentioning
confidence: 99%
“…These observations, combined with others on the regulatory effects of low-density lipoprotein, have led to the hypothesis (2) that the regulation of HMG-CoA reductase by sterols involves transcriptional or translational control of enzyme biosynthesis. Other studies (5) have provided evidence for a phosphorylation-dependent inactivation process for HMG-CoA reductase and have suggested that enzyme inactivation may also play a role in regulation of HMG-CoA reductase (6).…”
mentioning
confidence: 99%
“…AMPK is allosterically activated in response to an elevation in AMP-to-ATP ratio, and phosphorylation of threonine 172 residue of the α subunit by upstream kinases such as Liver Kinase B1 (LKB1) or calcium/calmodulin-dependent kinase kinase β increases the activity. [20][21][22][23][24][25][26][27] Recent studies have established a concept of AMPK as a key enzyme regulating metabolism. A variety of metabolic stresses and hormonal stimulations such as physical exercise, leptin and adiponectin have been reported to activate AMPK, which leads to lots of metabolic responses metabolome-widely including glucose uptake, fatty acid oxidation, and insulin sensitization etc.…”
mentioning
confidence: 99%